Integrasi Pendidikan Karakter dalam Pembelajaran di Sekolah Dasar : Membangun Generasi Cerdas dan Berintegritas (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Character education in elementary schools (SD) is an important aspect in shaping a young generation that not only possesses intellectual intelligence but also strong moral values. This article aims to explore how the integration of character education can be applied within the context of learning in elementary schools. This research uses a qualitative method with a literature study approach, reviewing various sources on character education in SD and its implementation practices. The research findings indicate that character education integration can be carried out through a thematic approach in the curriculum, active learning models, and the role of teachers as role models. Challenges faced include time and resource limitations, as well as a lack of cooperation with parents and the community. As solutions, there is a need for the development of a character-based curriculum, teacher training, and the enhancement of synergy between schools, parents, and the community.